Monetary Incentives and Employee Satisfaction: A Case of Access World Tech Pvt. Ltd. - Maharjan, Anina; Lamichhane, Basudev (Nepalese Journal of Business and Management Studies, 2022)
This research aims to examine the effect of monetary incentives on employee satisfaction among the employee of Access World Tech Pvt. Ltd., located at Krishnagalli, Patandhoka, Lalitpur. The study developed two research questions, two research objectives, and two hypotheses. Related literature was reviewed to develop a conceptual framework was reviewed. The study used a descriptive, relational, and causal research design considering the research objectives. The study’s population consists of 120 employees. The convenience sampling method was used in the study. The sample size of 92 was calculated using Maple Tech’s calculator. The close- end questionnaire was distributed to 110 respondents, 94 of whom were deemed valid. Because the item for the 5-point Likert scale was adopted from previous studies, the instrument used in the study is reliable and valid. The study’s conclusion was reached using statistical, descriptive, and inferential tools. The findings concluded that there is a positive and significant relationship between monetary incentives and employee satisfaction. Thus, the study discovered that monetary incentives have a direct effect on employee satisfaction.